AN ANALYSIS OF TABOO WORDS IN THE LYRICS OF LIMP BIZKIT ON ALBUM GOLD COBRA - AFANTA, YOHANES (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Taboo Words, Lyric, Limp BizkitNowadays, many songs have taboo inserted in the lyric to make the song more interesting to be listened. But, sometimes listeners misunderstand with the contexts meaning of taboo word in the songs. In order to avoid misunderstanding, the listener have to understand context meaning in the lyric than the listener understand what the purpose of the lyric that is created by the composer. This study analyzes taboo words in the lyrics of Limp Bizkit. The aim of this study is to find out: (1) the taboo words used in the lyrics of Limp Bizkit (2) the categorizations of taboo words used in the lyrics of Limp Bizkit. This study uses a qualitative approach. The data of this research are words, phrases, and sentences which contain taboo words. The source of the data is collected from the lyrics of Limp Bizkit’s songs which are taken from their official website.  The results of this research show that 21 kinds of taboo words are found in the lyrics. The categorization of taboo are devided into seven types of taboo, they are Mother in Law, Certain Game Animal, Sex, Death, Excretion, Bodily function, and Religious Matter. Only 1 of 12 songs does not contain taboo words. And there is no data found in The Left Hand type of taboo because that is strongly asociated with gestures. The researcher suggests that English learners should pay attention about the usage of taboo words in order to be able to use taboo words in proper circumstace. For other researchers, this research can give information and knowledge about Sociolinguistics especially taboo words.